HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN SELF EFFICACY MAHASISWA - Onik Wahyu Utami; Hening Tyas Arrido, Rogers Clinton Pittor, Rijal Abdilah (ADISAM PUBLISHER, 2024)
This research aims to analyze the relationship between social support and self-efficacy in students. Social support, which includes emotional, instrumental, informational, and reward support, is considered an important factor that can influence an individual's self-confidence in achieving academic and personal goals. Self-efficacy, or belief in one's ability to complete tasks and achieve goals, is a crucial aspect in student academic success. This research uses quantitative methods by distributing questionnaires to a number of students from various departments at a university. The results of the analysis show that there is a significant positive relationship between social support and self-efficacy. Students who receive high levels of social support tend to have higher levels of self-efficacy. These findings underscore the importance of a supportive social environment in increasing students' self-confidence to achieve academic success and personal well-being. This research suggests that educational institutions strengthen social support programs to help increase student self-efficacy.